Satisfaction of Old Age Allowance among Senior Citizen in Lamjung District, Nepal - Sendhai, Gopal Prasad (Kalika Journal of Multidisciplinary Studies, 2021)
The old age allowance is the non-contribution allowance provided by the government of Nepal to improve the social and economic status of older people. The purpose of this study was to compare the social and economic impact of old age allowance and its satisfaction on older people in rural and urban areas in Nepal. A cross sectional, quantitative study was conducted in two different areas (Sunderbazar municipality and Kwholasothar rural municipality) in Lamjung. The information was collected from 202 elderly people (55.4%) from urban and 90 (44.6%) from rural areas) to know about their satisfaction in various aspects like social, economic, health, etc. regarding allowance by face-to-face interview. Chi-square test, t-test as well as One-way ANOVA tests were applied to find the factors associated with the satisfaction of elderly people among rural and urban areas. Elderly in rural were more satisfied than elderly from urban areas. The respondents in rural areas were satisfied in all five domains social, health, economic, basic needs and self-esteem but the respondents in urban areas were found to be satisfied only in two domains; self-respect and economic. The satisfaction of respondents with OAA is different in urban and rural areas. People who were satisfied with this allowance reported that it was an honor from the government and they can use this money on their own. It is an important contribution to keeping older people connected with family and community.